[19]Dendriphene: A 19‐Ring Dendritic Nanographene. Issue 67 (8th November 2018) - Vilas‐Varela, Manuel; Fatayer, Shadi; Majzik, Zsolt; Pérez, Dolores; Guitián, Enrique; Gross, Leo; Peña, Diego
Abstract: The synthesis of a threefold symmetric nanographene with 19 cata ‐fused benzene rings distributed within six branches is reported. This flat dendritic starphene, which is the largest unsubstituted cata ‐condensed PAH that has been obtained to date, was prepared in solution by means of a palladium‐catalyzed aryne cyclotrimerization reaction and it was characterized on surface by scanning probe microscopy with atomic resolution. Abstract : Nanographenes : The successful synthesis of a dendritic nanographene is reported. [19]Dendriphene, which is the largest unsubstituted cata ‐condensed nanographene obtained by solution chemistry, was characterized on‐surface by scanning probe microscopy.